Perturbation Theory Methods for the Semiconductor Plasma Diode Simulation - Moroz, Igor; Bomba, Andrii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
A technique for solving a nonlinear singularly perturbed boundary value problem of predicting the state of an electron-hole plasma in the active region of p-i-n (plasma) diodes is considered. The problem is formulated for system of equations of the electron and hole currents continuity and the Poisson's equation. The solution to the problem is sought by the asymptotic method of boundary corrections. It is shown that boundary corrections play a key role in forming the electric field in the active region of the diode. Under certain conditions, boundary corrections demonstrate non-monotonic behavior. The presence of boundary corrections makes it possible to solve problems of heat distribution in the semiconductor device under study, problems of the influence of external electromagnetic fields on electron-hole plasma, etc. A series of computer experiments were conducted.